The Implementation of Scientific Approach to Increase Mathematical Understanding Ability on Junior High School Students - Putri Dyan Marini; Heris Hendriana; Aflich Yusnita Fitrianna; Muhammad Afrilianto (IKIP Siliwangi, 2023)
This research is motivated by the ability of mathematical understanding of students in Indonesia is still relatively low, students find it difficult to understand abstract mathematical concepts and mathematical understanding is not fully optimized and can be said to be still lacking, this condition is caused by a tendency to memorize and a little introduction to what is useful from the mathematical material studied. The purpose of this study is to implement a scientific approach to students' mathematical comprehension abilities. This research is a Classroom Action Research (PTK) using a spiral model from Kemmis and McTaggart with the stages being plan, action, observation or observation, and reflection for each cycle. The subjects in this study were grade VII students of Nur Al Rahman IT Junior High School for the 2022/2023 academic year with a total of 20 students. The material used is algebraic. The instrument used is a test instrument consisting of 7 mathematical understanding questions. The results of this study stated that students' mathematical understanding increased as evidenced by the increase in the percentage of question achievement indicators after 2 learning cycles. The percentage of cycle I results is low at 49%, while the percentage for cycle II is 81%. Based on the results of the study, the author concludes that implementing a scientific approach is an effort that can be done in the learning process to see or improve students' mathematical understanding.